2023
DOI: 10.3897/phytokeys.229.105457
|View full text |Cite
|
Sign up to set email alerts
|

Review of Orchidaceae of the northern part of Kazakhstan

Abstract: We present a review of Orchidaceae Juss. of the northern part of Kazakhstan, within the steppe, forest-steppe and semi-desert habitats of the country (Pavlodar, northern Kazakhstan, Kostanay, Akmola, Aktobe, West Kazakhstan, partially Karaganda and East Kazakhstan regions). The investigation is based on herbarium materials, literature data and field observations. We examined material from the following herbarium collections: LE, MW, TK, MHA, SVER, KUZ, ALTB, AA, NUR, KG, KSPI, NS, NSK, MOSP, ORIS, PPIU, totall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In many botanical centres in Kazakhstan, plant prospects are forecast based on visual (mainly phenological) observations. This approach gives good results but does not reveal the mechanisms of plant adaptation to unfavourable environmental conditions [43][44][45][46][47][48]. Previous studies of introduced plants' winter hardiness, water regime, and heat resistance have revealed some features of their adaptive response.…”
Section: Discussionmentioning
confidence: 99%
“…In many botanical centres in Kazakhstan, plant prospects are forecast based on visual (mainly phenological) observations. This approach gives good results but does not reveal the mechanisms of plant adaptation to unfavourable environmental conditions [43][44][45][46][47][48]. Previous studies of introduced plants' winter hardiness, water regime, and heat resistance have revealed some features of their adaptive response.…”
Section: Discussionmentioning
confidence: 99%